CD38 Deficiency Ameliorates Chronic Graft-Versus-Host Disease Murine Lupus via a B-Cell-Dependent Mechanism - Martínez-Blanco, África; Domínguez-Pantoja, Marilú; Botía-Sánchez, María; Pérez-Cabrera, Sonia; Bello-Iglesias, Nerea; Carrillo-Rodríguez, Paula; Martin-Morales, Natividad; Lario-Simón, Antonio; Pérez-Sánchez-Cañete, María M.; Montosa-Hidalgo, Laura; Guerrero-Fernández, Salvador; Longobardo-Polanco, Victoria M.; et al. (Frontiers in Immunology, 2021)
Absence of mouse cell surface receptor CD38 in Cd38-/- mice suggests that this receptor acts as positive regulator of inflammatory and autoimmune responses. Here we report that in the setting of a chronic graft versus host disease (cGVHD) lupus model induced by the transfer of B6.C-H2bm12/KhEg (bm12) spleen cells into co-isogenic Cd38-/- B6 mice causes milder lupus-like autoimmunity with lower levels of anti-ssDNA autoantibodies than the transfer of bm12 spleen cells into WT B6 mice. In addition, significantly lower percentages of Tfh cells, as well as GC B cells, plasma cells and T-bet+CD11chi B cells are observed in Cd38-/- mice than in WT mice, while the expansion of Treg cells, and Tfr cells is normal, suggesting that the ability of Cd38-/- B cells to respond to allogeneic help from bm12 CD4+ T cells is greatly diminished. The frequencies of T-bet+CD11chi B cells, which are considered the precursors of the autoantibody secreting cells, correlate with anti-ssDNA autoantibody serum levels, with IL-27, and sCD40L. Proteomics profiling of spleens from WT cGVHD mice reflects a STAT1-driven type I IFN-signature, which is absent in Cd38-/- cGVHD mice. Kidney, spleen and liver inflammation was mild and resolved faster in Cd38-/- cGVHD mice than in WT cGVHD mice. We conclude that in B cells CD38 functions as a modulator receptor that controls autoimmune responses. "Proteomic Data are available via ProteomeXchange with identifier PXD026947."